Pengaruh Terapi Perilaku Koqnitif Terhadap Gambaran Diri: Sistematika Review - Pangaribuan, Resmi; Sari, Putri Nanda (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2020)
Body image is a crucial factor in the formation of individual identity. Increasing body image on an individual requires an intervention which can change thoughts, feelings and attitudes affecting the behavior related to the whole body and its function. This systematic review evaluates the existed evidence to identify the effect of Cognitive Behavioral Therapy (CBT) on body image. The literature review is conducted by selecting the corresponding articles which are published between 2011 and 2017. Various databases used are CINAHL, EBSCO, Proquest, Pubmed, Science Direct, and Semantic Scholar. The inclusion criteria are the articles publishing original data, being fully written in English, researching human as an object and exploring the cognitive behavioral therapy and body image. There are eight articles that showed the effect of cognitive behavioral therapy on body image including reducing body image concern, reducing bad stigma towards body image and irrational beliefs on body changing, increasing body area satisfaction, improving appearance evaluation and improving a positive body image. The application of cognitive behavioral therapy is essential and effective in improving body image. This study recommends health professionals, especially nurses, to apply cognitive behavioral therapy in patients with various diseases involving body image disturbance.